PENGARUH CAPITAL ADEQUACY RATIO, RASIO BIAYA OPERASI ATAS PENDAPATAN OPERASI, RETURN ON ASSET TERHADAP NON PERFORMANCE LOAN BANK NASIONAL - M. UZAIR ACHMADI (Media Bisnis, 2014)
The purpose of this study is to examine the effect of capital adequacy ratio, biaya operasional atas pendapatan operasional and return on asset to non performance loan. This research consist of 20 Banks during the year 2007-2010 as a sample. Multiple regression method is used to analyze the research. The result of the research show that capital adequacy ratio and return on asset have positive influence to non performance loan. Biaya operasional atas pendapatan operasional has not influence to non performance loan.